The Effect of Red Ginger Drink Immersion on Surface Roughness of Acrylic Artificial Teeth - Veronica Angelia; Nuraisha Surraya; Nusima Mohamed (TALENTA, 2026)
Acrylic resin denture elements are popular due to their good aesthetics and economic value. However, their hydrophilic nature causes water absorption which can affect surface roughness. Red ginger drink contains phenolic compounds and is acidic. These compounds can diffuse into the acrylic resin matrix and break the polymer chain, potentially triggering surface damage. The purpose of this study was to determine the effect of the duration of immersion of conventional and intrahomogeneous polymer acrylic resin denture elements in red ginger drink for 3, 5, and 7 days on surface roughness. The laboratory experimental study used conventional and intrahomogeneous polymer acrylic denture elements samples (n = 40). The samples were divided into 4 treatment groups (each n = 10). The control group was immersed in artificial saliva, while the treatment group was immersed in red ginger drink. Surface roughness measurements were performed using a profilometer. Data were analyzed statistically using the Generalized Linear Model Repeated Measures (GLM-RM) test. The results showed a significant effect of the duration of immersion of acrylic denture elements in red ginger drink for 3, 5, and 7 days on the increase in surface roughness of both types of materials (p < 0.001). Conventional acrylic dentures showed a greater level of surface roughness compared to intra-homogeneous polymers, both in the control group and after immersion in the red ginger drink solution. Keyword: Acrylic artificial teeth, red ginger drink, surface roughness